Living with uncertain work. Issue 5 (18th October 2018) - Heyes, Jason; Moore, Sian; Newsome, Kirsty; Tomlinson, Mark
Abstract: This article examines the different forms of uncertainty that workers in precarious jobs experience on a day‐to‐day basis. The article highlights the various ways in which uncertainty at work spills over into workers' lives away from the workplace and provides a representative and up‐to‐date comparison of the experiences of workers in permanent, fixed‐term and casual forms of employment. The article achieves its objectives through a mixed‐methods research design comprising an analysis of data from the Understanding Society survey and interviews with workers in the retail, higher education, logistics and social care sectors.